Effect of foliar application of nano-nutrients solution on growth and biochemical attributes of tomato (Solanum lycopersicum) under drought stress - Mubashir, Areesha; Nisa, Zaib-un-; Shah, Anis Ali; Kiran, Munazza; Hussain, Iqtidar; Ali, Naila; Zhang, Lixin; Madnay, Mahmoud M. Y.; Alsiary, Waleed A.; Korany, Shereen Magdy; Ashraf, Muhammad; Al-Mur, Bandar A.; et al. (Frontiers in Plant Science, 2023)
Drought stress has drastically hampered the growth and yield of many crops. A pot experiment was conducted in the field area of University of Lahore. All laboratory analysis was carried out in General Botany Laboratory, Institute of Molecular Biology and Bio-technology, UOL Lahore. Tomato seedlings which were obtained from vegetables research institute, AARI Faisalabad. Seedlings were transplanted into pots at 2-3 leaf stage, each filled with loam-compost-organic manure soil (3:1:1). This experiment was designed in a completely randomized design (CRD) with three replications. Plants were grown till the fruit formation/yielding stage. Plants were divided into two groups. (a) control group (b) applied stress group. Plants at vegetative stage were treated with 100% FC for control group and 60% FC for drought group, and these levels were maintained until harvesting. Both the groups (control and drought stress) were foliar sprayed with nano-nutrient solution. Three treatments of nano-nutrient solution with four levels i.e., 0%, 1%, 3% and 5% were given to all the pots after two weeks of drought stress treatment with a gap of 5 days at vegetative stage. 1% application displayed an improvement in shoot length, shoot fresh and dry weight, number of leaves and flowers. Leaf pigments like chlorophyll a, b, total chlorophyll and carotenoids and total phenolics contents were found maximum while minimum electrolyte leakage was observed at 3% application compared to control. Further, 1% application of NNS increased the Leaf RWC%, total soluble sugars, flavonoids contents. 5% NNS application exhibited higher total free amino acids with minimum lipid peroxidation rate in leaves of tomato under drought. Antioxidant enzyme activities increased in a concentration dependent manner as gradual increase was observed at 1%, 3% and 5%, respectively.